Review of Cephennomicrus and Pomphopsilla of the Seychelles (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
All species of the cephenniine genus Cephennomicrus known to occur in the Seychelles were described by Scott (as Neseuthia) nearly a century ago. The descriptions were based on external characters, which does not allow for species identification. All the species are redescribed here: C. cordithorax, C. cornutus, C. minor, C. perexiguus, C. politus and C. typicus. Cephennomicrus crenatus is transferred to another genus, resulting in Pomphopsilla crenata comb. n. Lectotypes are designated for Neseuthia minor, N. perexigua and N. crenata. A new species group within Cephennomicrus is proposed to accommodate all species treated here, which share, among other characters, a long flagellum with a broad proximal portion, very short setae on the pronotum and elytra, five pronotal antebasal pits, a transverse groove connecting three of them, and unique modifications of the head in males.